(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The response of photovoltaic (PV) panel temperature is change with respect to the altering in the arriving solar radiation. A transient thermal model is predicted to investigate the temperature distribution of a solar panel, which includes the materials composition of panel, by effecting thermal and the optical properties of these materials. A new thermal model is propounded that desegregates conditions of atmospheric, impacts of panel materials behavior and mounting structure. Also, it is observed solar cell temperature has a decisive role in ruling the parameters produce. The results are indicated that the created model compatible with different types of (PV) module. The model has been advocated by measurements of the cell back surface temperature and solar irradiation through a period of time. A free convective heat transfer loss from the rear surface is analyzed.